Play-Based Activities with a CoderBot Robot on a Pediatric Ward: A Case Study - Castiglioni, Marco; Caldiroli, Cristina Liviana; Antonietti, Alessandro (Healthcare (Basel), 2022)
Being hospitalized is a threatening and stressful experience for many children. From a psychological point of view, children may experience increased feelings of anxiety and fear that can negatively influence their behavioral, cognitive, and emotional outcomes. To mitigate such adverse effects on children’s mental health and well-being, interventions that might contribute to protecting the emotional domain of hospitalized children are welcome. The present case study of a single-setting intervention allowed us to evaluate the impact, on children admitted to a pediatric short-term recovery ward (N = 61), of participating in play-based activities with a CoderBot robot. The methodology spanned multiple data sources (children, parents, nurses), field observation, and a sequential (quantitative–qualitative) mixed-method approach to data analysis. We found that robot-based activities are associated with enhanced well-being (particularly positive emotions). Both the participating children and their caregivers reported that the activity was enjoyable and interesting, especially thanks to its technologically innovative nature. We critically discuss these positive findings in relation to the strengths of our pilot study, as well as its contextual and methodological limitations, and outline possible future lines of development for this kind of project.